2018
DOI: 10.1037/cdp0000170
|View full text |Cite
|
Sign up to set email alerts
|

Racial identity invalidation with multiracial individuals: An instrument development study.

Abstract: The findings highlight the different dimensions of racial identity invalidation and indicate their negative associations with connectedness and psychological well-being. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 67 publications
2
74
0
Order By: Relevance
“…Though mislabeling fits under the general umbrella of these terms, mislabeling is more specific and speaks to the verbal assumptions (via labels) by others about Multiracial identity. This is in contrast to denying one's racial identity, which describes racial invalidation (Franco & O'Brien, 2018).…”
Section: The Concept Of Mislabelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Though mislabeling fits under the general umbrella of these terms, mislabeling is more specific and speaks to the verbal assumptions (via labels) by others about Multiracial identity. This is in contrast to denying one's racial identity, which describes racial invalidation (Franco & O'Brien, 2018).…”
Section: The Concept Of Mislabelingmentioning
confidence: 99%
“…The findings related to the theme perceptions of race have major implications for our society and especially for the practice of counseling and training. Due to the growing racial milieu of U.S. society (Charmaraman, Woo, Quach, & Erkut, 2014), it is important for those living in the United States to understand that race is not as simple as skin tone, as it is a complex social construction (Franco & O'Brien, 2018;Tran et al, 2016). It is especially important for professional counselors, educators, and supervisors working from a foundation of wellness (Kaplan, Tarvydas, & Gladding, 2014) to build upon this foundation utilizing an understanding of the social construction of race (Giamo et al, 2012;Terry & Winston, 2010).…”
Section: Counselor Practice and Training Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, research examining multiracial‐specific racial stressors and well‐being have used only self‐report measures. These studies have found relationships between discrimination and poorer psychological health (e.g., Franco & O'Brien, 2018; Sanchez, Shih, & Garcia, 2009). However, individuals completing self‐report measures underreport stress, even when their bodies exhibit physiological reactions (Clark et al, 1999; Peters et al, 2011).…”
mentioning
confidence: 99%